Household Waste Management Policy Challenges and Opportunities: Tantangan dan Peluang dalam Kebijakan Pengelolaan Sampah Rumah Tangga - Achmad Fawwaz Albani; Shorea Helminasari; Ahmad Yani; Deandlles Christover (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Waste management remains a critical environmental and public health issue in Indonesia, affecting both urban and rural communities. Specific Background: In Kelinjau Ulu Village, East Kutai Regency, rising household waste generation is exacerbated by insufficient infrastructure, limited processing facilities, and suboptimal local policy enforcement. Knowledge Gap: While regional waste strategies are mandated, little empirical evidence exists on how these are operationalized at the village level and the local factors influencing success or failure. Aims: This study analyzes the direction and implementation of household waste management policy in Kelinjau Ulu Village, focusing on waste separation, collection, transportation, and disposal, as well as identifying enabling and constraining factors. Results: Employing a qualitative descriptive approach through observation, interviews, documentation, and literature review, findings reveal that although policy frameworks are comprehensive, implementation is hindered by inadequate facilities and infrastructure, while community awareness and government support serve as enabling factors. Novelty: This research offers a detailed, village-scale assessment of household waste policy implementation challenges, bridging the gap between regional strategies and local realities. Implications: Strengthening infrastructure, enhancing community engagement, and enforcing regulations are crucial for improving rural waste management policy effectiveness in Indonesia. Highlights: Infrastructure limitations significantly hinder effective household waste management in rural areas. Community awareness and local government support are key enabling factors for policy success. Village-level analysis reveals practical gaps between regional strategies and on-the-ground implementation. Keywords: Household Waste Management, Policy Implementation, Rural Infrastructure, Community Engagement